Connections of the mouse orbitofrontal cortex and regulation of goal-directed action selection by BDNF-TrkB - Zimmermann, Kelsey S. (Biol Psychiatry, 2015)
BACKGROUND: Distinguishing between actions that are more, or less, likely to be rewarded is a critical aspect of goal-directed decision-making. However, neuroanatomical and molecular mechanisms are not fully understood. METHODS: We used anterograde tracing, viral-mediated gene silencing, functional disconnection strategies, pharmacological rescue, and Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) to determine the anatomical and functional connectivity between the orbitofrontal cortex (oPFC) and the amygdala in mice. In particular, we knocked down Brain-derived neurotrophic factor (Bdnf) bilaterally in the oPFC, or generated an oPFC-amygdala “disconnection” by pairing unilateral oPFC Bdnf knockdown with lesions of the contralateral amygdala. We characterized decision-making strategies using a task wherein mice select actions based on the likelihood that they will be reinforced. Additionally, we assessed the effects of DREADD-mediated oPFC inhibition on the consolidation of action-outcome conditioning. RESULTS: As in other species, the oPFC projects to the basolateral amygdala and dorsal striatum in mice. Bilateral Bdnf knockdown within the ventrolateral oPFC, and unilateral Bdnf knockdown accompanied by lesions of the contralateral amygdala, impede goal-directed response selection, implicating BDNF-expressing oPFC projection neurons in selecting actions based on their consequences. The TrkB agonist 7,8-dihydroxyflavone rescues action selection and increases dendritic spine density on excitatory neurons in the oPFC. Rho-kinase inhibition also rescues goal-directed response strategies, linking neural remodeling with outcome-based decision-making. Finally, DREADD-mediated oPFC inhibition weakens new action-outcome conditioning. CONCLUSIONS: Activity- and BDNF-dependent neuroplasticity within the oPFC coordinate outcome-based decision-making through interactions with the amygdala. These interactions brake reward-seeking habits, a putative factor in multiple psychopathologies.